Strategies for Strengthening Student Character from an Independent Curriculum Perspective - Muallifah, Ilun; Yusuf, Arba’iyah; Karim, Abdul Rahim (ISTAWA, 2024)
Strengthening national character is vital to the quality of a generation. The government needs to establish character education policies that are relevant to be put into practice today. The independent curriculum offers a simpler and more ideal educational concept that places teachers and students as subjects in learning activities. This research aimed to study whether the independent curriculum facilitates the strengthening national character, and to what extent. This research was conducted using the library method through a qualitative approach, with the data analysis done by means of content analysis techniques. Research findings show that the character strengthening strategy in the Merdeka curriculum is contained in the Pancasila Student Profile concept with a series of curriculum policies including the educational ecosystem, teachers, pedagogy, curriculum and assessment systems. Strengthening the Pancasila Student Profile is actualized in students' daily lives through school culture, intracurricular learning, Project for Strengthening Pancasila Student Profiles (P5), and interest and talent development activities (extracurricular). Meanwhile, the values contained in the Pancasila Student Profile include faith and devotion to God Almighty, noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity.